Sharing linked data for health research toward better decision making - Adams, Carolyn 1962-; Flack, Felicity 1969-; Allen, Judy 1953- (Cambridge bioethics and law, 2022)
Health research around the world relies on access to data, and much of the most valuable, reliable, and comprehensive data collections are held by governments. These collections, which contain data on whole populations, are a powerful tool in the hands of researchers, especially when they are linked and analyzed, and can help to address "wicked problems" in health and emerging global threats such as COVID-19. At the same time, these data collections contain sensitive information that must only be used in ways that respect the values, interests, and rights of individuals and their communities. Sharing Linked Data for Health Research provides a template for allowing research access to government data collections in a regulatory environment designed to build social license while supporting the research enterprise